Characterisation of treated domestic wastewater and its potential use for small scale urban agriculture in Bulawayo: balancing health and environmental needs - Makoni, Fungai Sexton Ndawana (University of the Free State, 2014)
The use of urban wastewater for agriculture crop production is receiving renewed attention in most parts of the world due to the increasing scarcity of water. Water scarcity has placed pressure on the ability of households to meet their basic needs as the intermittent supply of water has created a demand for other sources of water, such as wastewater for irrigation, which can either be expensive or dangerous to public health. In this regard it might seem obvious to view wastewater as a major source of water for Bulawayo, Zimbabwe, particularly for irrigation. The general objective of the study was to characterise and determine treated domestic wastewater parameters that are of agricultural, public health and environmental importance for use in urban agriculture irrigation in Bulawayo. The study critically assessed the wastewater quality being used for urban agriculture in relation to its characteristics, the possible impacts on environment health and also quantifying the socio economic factors that can be derived from its use and, based on this assessment, to formulate a strategy for sustainable treated domestic wastewater use for irrigation. Data collection for this study was conducted in Bulawayo urban area and the gum plantation from 2005 - 2010. Extensive wastewater quality analysis was carried out and results of effluent analysis of key parameters, nitrogen and phosphorous were found to be 11.5 mg/l ± 4.4 and 13.5 mg/l ±14.9 respectively, which were within the World Health Organisation (WHO) (2006) acceptable range. These results aided to confirm that the treated domestic wastewater is of acceptable quality and hence has potential to be used for irrigating crops such as maize, beans and vegetables (chomolier) with minimal risk. Effluent heavy metals concentration in the form of Cadmium (Cd) and lead (Pb) measured values of 0.027 mg/l ± 0.01 and 0.45 mg/l respectively and were within the acceptable levels according to the WHO guidelines and Zimbabwe National Water Authority (ZINWA) standards. Heavy metal soil content was also observed to be within the acceptable limits with both Cd and Pb showing strong correlation with soil pH (r2= 1). Vegetable tissue analysis did not detect any significant levels of Cd and Pb in vegetable samples including Chomolier (not detected),maize (not detected), and beans (not detected), which then confirmed the conclusion that the treated domestic wastewater has potential for agricultural irrigation provided the quality of the effluent would not change drastically from the observed status which was measured over five years. With regard to social acceptance and economic benefits, the study revealed that acceptance for use of treated domestic wastewater and consumption of produce from its use was high amongst the farmers with 88.9% of respondents acknowledging no problem in using the treated domestic wastewater. Estimation of financial benefits were derived using the conventional market based approach which then revealed that an income of about US$1000 per plot/year is feasible if a proper management system is put in place. Findings of this study confirm that use of treated domestic wastewater for urban irrigation can improve livelihoods of the resource limited farmers despite the health challenges associated with its use. Majority of the famers reported that use of treated domestic wastewater for agriculture has contributed significantly to their socio- economic lifestyles by making extra income to cover school fees (44.6%), medication (9.85%) and food (99.1%). Apart from the financial benefits observed, calculations using the FAO formula for nutrient contribution, the study indicated that the treated domestic wastewater which was used contributed approximately 92 kg/ha/year, 108 kg/ha/year and 281.6 kg/ha/year of nitrogen, phosphorus and potassium respectively hence improving soil fertility of the sandy loam soils found at the farming area. Evaluation of the findings in relation to the recommended guidelines and standards of Food and Agricultural Organisation (FAO)/WHO and ZINWA suggests that the treated domestic wastewater used at the gum plantation is suitable for crop irrigation specifically for the following crops: chomolier, maize and beans that were investigated over time. In addition the benefits of using the treated domestic wastewater were noted to have the potential to enhance proper management of wastewater irrigation as proposed in the strategy as it proved to be a reliable water resource. Adherence to the strategy that is proposed in this thesis of involving stakeholders, addressing policy and legal issues, supporting research and outreach, marketing and periodic monitoring of effluent, soil and plant quality parameters will ensure successful, safe, long-term wastewater irrigation that will balance human and environmental needs.
Thesis (Ph.D. (Zoology and Entomology))--University of the Free State, 2014
Keywords: Water reuse -- Zimbabwe -- Bulawayo; Water-supply -- Zimbabwe -- Bulawayo; Urban agriculture -- Zimbabwe -- Bulawayo; Sewage -- Environmental aspects -- Zimbabwe -- Bulawayo; Livelihoods; Water resource; Agriculture; Effluent; Public health; Environment; Wastewater use